On some known fixed point results in the complex domain: survey - Došenović, Tatjana M.; Koppelaar, Henk; Radenović, Stojan N. (Vojnotehnički glasnik / Military Technical Courier, 2018)
In this survey paper, we consider some known results from the fixed point theory with complex domain. The year 1926 is very significant for this subject. This is the beginning of the research and application of the fixed point theory in complex analysis. The Denjoy-Wolf theorem, together with the Banach contraction principle, is one of the main tools in the mathematical analysis.
Keywords: fixed point; Jordan curve; analytic function; complex Banach space